High achievers' perspectives on the existence and significance of love of learning / Nadia Mohd Dani Goh - Mohd Dani Goh, Nadia (Faculty of Education, 2011)
This research is aimed to investigate the existence and the significance of Love of Learning among high achievers at the International Education Centre (INTEC) through semi-guided interview questions. Five respondents were interviewed to define the meanings attached to the Love of Learning and their reasons for learning among high achievers, the symptoms/characteristics and the significance of love of learning. The findings proved that high achievers perceived that the Love of Learning exists among high achievers with the meanings attached that are attachment to an outside object, intelligent care and concern for the subject, humility/ selflessness, . longing for understanding, interest/ passion/enthusiasm, intrinsic motivation/ autonomous learning and perseverance. The Love of Learning is perceived as important to promote life-long learning, autonomous learning, and the joy of learning besides ensuring the stability in life, improving the standard of living among the society within the learning society and attaining success for personal achievement. This research is hoped to contribute to the literature and ignite future researchers’ interest in the issue, Love of Learning.